(untitled) - Timberg, Robert (New York, 1995)
Robert Timberg weaves together the lives of Annapolis graduates John McCain, James Webb, Oliver North, Robert McFarlane, and John Poindexter to reveal how the Vietnam War continues to haunt America. Casting all five men as metaphors for a legion of well-meaning if ill-starred warriors, Timberg probes the fault line between those who fought the war and those who used money, wit, and connections to avoid battle. A riveting tale that illuminates the flip side of the fabled Vietnam generation
Keywords: Hoa Kỳ,United States; Quan hệ đối ngoại,Foreign relations; 1981-1989,1981-1989